Evaluation of the successful implementation of creative audio media models in early childhood education in Yogyakarta - Rahayu Retnaningsih; Samsi Haryanto; Puspa Eka Ayu Febriana (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to describe the successful application of audio media for the creation of early childhood development models in terms of reactions and aspects of the learning process. The method used is descriptive qualitative method implemented in Kindergarten Yogyakarta, Indonesia. The research subjects were determined using a purposive sampling technique where the research subjects were selected according to the research objectives. The research subjects include teachers and kindergarten students. Data was collected using direct observation/observation methods, and in-depth interview methods. The standard of data validity in qualitative research refers to the standards of credibility, transferability, dependability, and confirmability. The data analysis technique used is descriptive qualitative analysis with data reduction techniques, data presentation, and drawing conclusions. The conclusion of this research is the application of audio media for the creation of early childhood development models in terms of reactions and the learning process is suitable to be applied in early childhood schools, because it is interesting for students, makes the atmosphere fun, and creates joy in learning, students are very enthusiastic, students always active in practicing the steps according to the material presented in audio media.